2022
DOI: 10.34172/jcvtr.2022.06
|View full text |Cite
|
Sign up to set email alerts
|

The fate of the fresh autologous pericardium after right ventricular outflow tract reconstruction

Abstract: Introduction: The autologous pericardium, treated or fresh, is used in reconstructive cardiovascular surgery. We aimed to describe the features of fresh pericardium utilized in right ventricular outflow tract (RVOT) reconstruction, years after the initial surgery. Methods: This cross-sectional study was performed on 72 patients (65.3% male, mean age =18.68 ± 9.63 y) with a history of RVOT reconstruction with the fresh autologous pericardium who underwent reoperation. During the surgery, a 1 × 1 cm sample was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Importantly, the significance of the potential complication of dilatation is not universally agreed upon, and some researchers maintain that the benefits of fresh autologous pericardium outweigh the potential risks [ 23 ]. A recently published study by Tatari et al demonstrated outcomes of fresh autologous pericardium RVOT patches at a mean follow-up interval of 13.48 ± 7.38 years [ 23 ]. Of a 72-patient cohort, 53 (73.6%) showed no RVOT dilatation, 17 (23.6%) showed mild RVOT dilatation, and 2 (2.8%) had RVOT aneurysms [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, the significance of the potential complication of dilatation is not universally agreed upon, and some researchers maintain that the benefits of fresh autologous pericardium outweigh the potential risks [ 23 ]. A recently published study by Tatari et al demonstrated outcomes of fresh autologous pericardium RVOT patches at a mean follow-up interval of 13.48 ± 7.38 years [ 23 ]. Of a 72-patient cohort, 53 (73.6%) showed no RVOT dilatation, 17 (23.6%) showed mild RVOT dilatation, and 2 (2.8%) had RVOT aneurysms [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recently published study by Tatari et al demonstrated outcomes of fresh autologous pericardium RVOT patches at a mean follow-up interval of 13.48 ± 7.38 years [ 23 ]. Of a 72-patient cohort, 53 (73.6%) showed no RVOT dilatation, 17 (23.6%) showed mild RVOT dilatation, and 2 (2.8%) had RVOT aneurysms [ 23 ]. In the same study, histologic analysis confirmed the positivity of explanted patches for CD31, CD34, smooth muscle alpha-actin, and von Willebrand factor (VWF) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations